Hyperbaric Oxygen Increases Stem Cell Proliferation, Angiogenesis and Wound-Healing Ability of WJ-MSCs in Diabetic Mice - Peña-Villalobos, Isaac; Casanova-Maldonado, Ignacio; Lois, Pablo; Prieto, Catalina; Pizarro, Carolina; Lattus, José; Osorio, Germán; Palma, Verónica (Frontiers in Physiology, 2018)
Hyperbaric oxygen therapy (HBOT) is effective for the medical treatment of diverse diseases, infections, and tissue injury. In fact, in recent years there is growing evidence on the beneficial effect of HBOT on non-healing ischemic wounds. However, there is still yet discussion on how this treatment could benefit from combination with regenerative medicine strategies. Here we analyzed the effects of HBOT on three specific aspects of tissue growth, maintenance, and regeneration: i) modulation of adult rodent (Mus musculus) intestinal stem cell turnover rates; ii) angiogenesis dynamics during the development of the chorio-allantoic membrane (CAM) in Gallus gallus embryos; iii) and wound-healing in a spontaneous type II diabetic mouse model with a low capacity to regenerate skin. To analyze these aspects of tissue growth, maintenance, and regeneration, we used HBOT alone or in combination with cellular therapy. Specifically, Wharton Jelly Mesenchymal Stem cells (WJ-MSC) were embedded in a commercial collagen-scaffold. HBOT did not affect the metabolic rate of adult mice nor of chicken embryos. Notwithstanding, HBOT modified the proliferation rate of stem cells in the mice small intestinal crypts, increased angiogenesis in the CAM, and improved wound-healing and tissue repair in diabetic mice. Moreover, our study demonstrates that combining stem cell therapy and HBOT has a collaborative effect on wound-healing. In summary, our data underscore the importance of oxygen tension as a regulator of stem cell biology and support the potential use of oxygenation in clinical treatments.